2005
DOI: 10.1371/journal.pgen.0010016
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor-Dependent Gene Regulatory Networks

Abstract: While the molecular mechanisms of glucocorticoid regulation of transcription have been studied in detail, the global networks regulated by the glucocorticoid receptor (GR) remain unknown. To address this question, we performed an orthogonal analysis to identify direct targets of the GR. First, we analyzed the expression profile of mouse livers in the presence or absence of exogenous glucocorticoid, resulting in over 1,300 differentially expressed genes. We then executed genome-wide location analysis on chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(108 citation statements)
references
References 75 publications
5
103
0
Order By: Relevance
“…In general, we were struck by the remarkable degree of cell and gene specificity inherent in androgen regulation, as 182 (89%) of the 205 ARGs we identified were apparently androgen-unresponsive in LNCaP cells (DePrimo et al 2002;Nelson et al 2002). Similarly, comparisons of glucocorticoid-responsive genes in different cell types (Rogatsky et al 2003;Wang et al 2004;Phuc Le et al 2005;So et al 2007) revealed little overlap. It will be important in future work to assemble expression and response data from multiple androgen-responsive cell types to better define and understand tissue-specific transcriptional networks radiating outward from AR.…”
Section: Figure 6 Distribution Analysis Of Ares Located Near Args (A)mentioning
confidence: 94%
See 1 more Smart Citation
“…In general, we were struck by the remarkable degree of cell and gene specificity inherent in androgen regulation, as 182 (89%) of the 205 ARGs we identified were apparently androgen-unresponsive in LNCaP cells (DePrimo et al 2002;Nelson et al 2002). Similarly, comparisons of glucocorticoid-responsive genes in different cell types (Rogatsky et al 2003;Wang et al 2004;Phuc Le et al 2005;So et al 2007) revealed little overlap. It will be important in future work to assemble expression and response data from multiple androgen-responsive cell types to better define and understand tissue-specific transcriptional networks radiating outward from AR.…”
Section: Figure 6 Distribution Analysis Of Ares Located Near Args (A)mentioning
confidence: 94%
“…Rather than focusing primarily on promoter proximal regions (Phuc Le et al 2005) or CpG islands (Weinmann et al 2002) or individual chromosomes , we developed tiled-oligonucleotide microarrays spanning ∼104 kb centered on the predicted transcription start site of each of several hundred candidate hormone-responsive genes. We assessed the relationship between receptor occupancy and hormone responsive expression, characterized the genomic organization of AR-regulated genes and AREs, surveyed the complexity and composition of the AREs, and examined the physiologic roles of the primary ARGs.…”
mentioning
confidence: 99%
“…Immunoprecipitated DNA was amplified to linear phase by ligation-mediated PCR as described (20). Amplified DNA was labeled using Genisphere's DNA900 labeling system (Genisphere, Hatfield, Pennsylvania) and hybridized as described fully in Supplement 1.…”
Section: Amplification Of Chip Dna and Microarray Analysismentioning
confidence: 99%
“…The current study is the first to demonstrate that uterine MCs are immunopositive for nuclear GR. A glucocorticoid rich environment would favour activation of GR, with shuttling of ligand activated receptor from the cytoplasm towards the nucleus ( Phuc Le et al ., 2005). This observation would be consistent with expression 11-β hydroxysteroid dehydrogenase enzymes within the uterus, resulting in a cortisol rich microenvironment ( Gibson et al ., 2013; McDonald et al , 2006).…”
Section: Discussionmentioning
confidence: 99%